2001
DOI: 10.1046/j.1432-1327.2001.01912.x
|View full text |Cite
|
Sign up to set email alerts
|

New pathway of amine oxidation respiratory chain of Paracoccus denitrificans IFO 12442

Abstract: The physiological electron acceptor of quinohemoprotein amine dehydrogenase (QH-AmDH) from Paracoccus denitrificans IFO 12442 was identified by biochemical and electrochemical methods. Of three types of heme c-containing proteins purified together with QH-AmDH from the periplasm of n-butylamine-grown cells, only constitutive cytochrome c-550 was reduced by the addition of QH-AmDH and n-butylamine. Reconstitution of the respiratory chain revealed that cytochrome c-550 mediates the electron transfer from QH-AmDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Partial reduction of the enzyme by dithionite gave a semiquinone radical EPR signal similar to that of TTQ in MADH. Cytochrome c 550 has been shown to be the natural electron acceptor for QHNDH (11). A similar QHNDH has been isolated from Pseudomonas putida, but apparently with somewhat different subunit composition and with exogenous electron acceptor specificity for azurin (12).…”
mentioning
confidence: 99%
“…Partial reduction of the enzyme by dithionite gave a semiquinone radical EPR signal similar to that of TTQ in MADH. Cytochrome c 550 has been shown to be the natural electron acceptor for QHNDH (11). A similar QHNDH has been isolated from Pseudomonas putida, but apparently with somewhat different subunit composition and with exogenous electron acceptor specificity for azurin (12).…”
mentioning
confidence: 99%
“…16) The purified heme 2 showed two bands, of molecular masses 59.5 kDa and 36.5 kDa, on SDS-PAGE. 16) From these results, heme 2 protein appears to be very similar to QHAmDH in certain physical properties, although it has no catalytic activity for amine oxidation. In this study, we found that heme 2 protein was slowly activated in 10-30 h during incubation with n-butylamine, one of the major substrates of QH-AmDH (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…QH-AmDH and heme 2 protein from P. denitrificans were isolated and purified as described in the literature. 16) The concentration of the reduced proteins was determined from the absorbance at 552 nm (" ¼ 37:2 mM À1 cm À1 ). The fully oxidized and reduced forms of QH-AmDH and heme 2 were prepared by adding K 3 Fe(CN) 6 and n-butylamine (or Na 2 S 2 O 4 ) respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations